A new formulation of continuous transverse shear stress field for static and dynamic analysis of sandwich beams with soft core - Ren, Shanhong; Zhao, Guozhong (International journal for numerical methods in engineering, 2020)
Summary This article presents a novel formulation for sandwich beams with soft core based on a layerwise description of continuous transverse shear stress field. The transverse shear stress field is assumed to follow a quadratic distribution in thick face layers and a uniform distribution in soft core. Based on stress‐strain relations, transverse shear strain is obtained, and in‐plane displacement field is determined by taking the integral of the transverse shear stain. By enforcing interlaminar displacement continuity, an explicit displacement field expression containing only displacement variables is formulated. In this formulation, interlaminar continuity conditions of displacement and transverse shear stress are satisfied simultaneously, and transverse shear and crosssectional warping effects in thick face layers are accurately taken account. To show characteristics and advantages of the present model, some classical theoretical models are further developed under different kinematic assumptions. The governing equations are derived using Hamilton principle, and finite element solutions for static and dynamic analysis of sandwich beams are presented. Comparisons with exact solution and other well‐known solutions, well demonstrate high accuracy of the present model for sandwich beams with different features. Besides, numerical discussions further reflect accuracy advantages of the present model in static and dynamic analysis of sandwich beams.